DESAIN PEMBELAJARAN INTERAKTIF STRATEGI PROBLEM BASED LEARNING BERBASIS PRAKTIKUM BERBANTUAN APLIKASI ATLAS - Sanda Patrisia Komalasari (Ensiklopedia of Journal, 2023)
The purpose of this study is to provide recommendations about design of interactive learning models with practical problem based learning teaching strategies assisted by ATLAS applications in auditing courses. This study also aims to see how students' opinions regarding the implementation of the learning designs that have been made. Literature review used to make learning designs and experimental methods and survey of 14 students was conducted to see the results of the implementation. The results show that there is an increase in student scores as much as 20% from the test results before and after learning is carried out. Students also feel that they understand better and feel that the ATLAS application is useful in guiding them in carrying out ISA audit based. The existence of teamwork makes the student ability of team work and leadership to be better. Students also think that the existence of a reward system motivates them more in learning.